EFFICIENCY OF COMBINED ANTIHYPERTENSIVE THERAPY IN PATIENTS WITH ARTERIAL HYPERTENSION AND OBESITY DEPENDING ON THE POLYMORPHISM OF CYP2C9 GENE - F. A. Kovalenko; V. V. Skibitsky; A. V. Fendrikova; K. Yu. Lazarev; I. A. Lukonin (Кубанский научный медицинский вестник, 2018)
Aim. To assess the efficiency of combined antihypertensive therapy in patients with arterial hypertension and obesity depending on the polymorphism of CYP2C9 gene.Materials and methods. Patients with uncontrolled arterial hypertension (1-2 stage) and obesity were included in our study. They were randomized by the method of "converts" into two groups: the first group (n=70) took the fixed-dose combinations of the valsartan and amlodipine and the second group took the fixed-dose combinations of the perindopril and amlodipine. Blood pressure of all patients was measured according to the recommendation for diagnosis and treatment of arterial hypertension (ESH/ESC, 2013) before and after 8 weeks of the initial treatment. All tested people had venous blood sampling succeeded by DNA extraction and amplification in real time mode polymorphic variants CYP2C9 gene. The improvement of health self-esteem by QALY was determined like increase of index from initial by 10 % and more.Results. It is shown that people with heterozygosis polymorphisms *1/*2 and *1/*3 reached the target level of arterial blood pressure after 8 weeks of combined therapy of valsartan and the amlodipine (93,1% against 57,1% respectively). In addition to the above, the frequency of reaching the target level of the arterial blood pressure in the group of tested people who get angiotensin II receptor blocker and calcium-channel blocker was for certain higher among the patients with polymorphisms *1/*2 and *1/*3 in comparison with the polymorphic variants CYP2C9 gene (91,3% against 57,1% respectively). The improvement of the health self-esteem by QALY of the tested patients with polymorphisms *1/*2 and *1/*3 CYP2C9 gene is seen more often between the patients of the first group than between patients of the second group (95,6% against 66,7% respectively).Conclusion. Determined interrelation between the efficiency level of the combined antihypertensive therapy with the CYP2C9 gene polymorphism can be considered in cases of insufficient effect of assigned therapy or the uncontrolled character of the arterial hypertension. In our opinion, appropriate personalized correction of therapy will contribute to its optimization relating to the patients with arterial hypertension and obesity.